Functional adaptive resources for large herbivores in African savannas: an ecological-gradient based framework - Fynn, Richard W. S.; Provenza, Frederick D. (Frontiers in Conservation Science, 2023)
The viability of large herbivore populations in the face of climate change, environmental variability, disease and predation will be determined by their freedom to assess and respond to these factors through access to a range of functional seasonal resources and habitats. Their responses will be contingent upon various organismal traits, such as body size, mouth and digestive anatomy, which also facilitate coexistence among sympatric species. In this paper we develop a functional adaptive forage resource framework based on plant biomass, quality and phenology responses on ecological productivity gradients. We show how large herbivores coexist and respond to environmental variability, disease and predation by their foraging responses in relation to functional adaptive resources, as mediated by their anatomical traits. Below a critical body size, where predation limits population size, large herbivores adopt a variety of predation avoidance strategies, which are linked to their anatomical traits and foraging strategies. Mouth anatomy, and its interaction with body size, appears to be the major anatomical trait determining large herbivore selection for grass height. Body size is the major trait determining vulnerability to predators. Ecological productivity gradients underlain by variation in soil moisture availability over the annual cycle support high quality forage in the least productive (driest) regions, which promote growth and reproduction (a fecundity resource). Reserves of adequate quality forage in moderate productivity regions and buffers of low-quality forage in wetter and more productive regions of the gradient prevent loss of body stores over the dry season and starvation during droughts. Fire and grazing contribute towards providing high quality forage by removing old, low-quality material and preventing forage maturation. Consuming a high diversity of plant species distributed across ecological gradients promotes phytochemical diversity in the diet, which functions as medicinal resources to promote health while combating disease and parasites. Large herbivores are becoming increasingly restricted by ecosystem fragmentation in their access to the full range of these functional resource classes. The negative consequences for large herbivore populations of reduced access to these resource classes is compounded by climate change, where conditions are hotter and drought frequency and intensity is expected to be higher